2014
DOI: 10.4161/hv.34366
|View full text |Cite
|
Sign up to set email alerts
|

A novel plant-produced Pfs25 fusion subunit vaccine induces long-lasting transmission blocking antibody responses

Abstract: Malaria transmission blocking vaccines (TBV) directed against proteins expressed on sexual stages of Plasmodium falciparum in the mosquito midgut are considered an effective means to reduce malaria transmission. Antibodies induced by TBV block sporogonic development in the mosquito, and thus transmission to the next human host. The Pfs25 protein, expressed on the surface of gametes, zygotes and ookinetes, is one of the primary targets for TBV development. Using a plant virus-based transient expression system, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Currently, many efforts for the development of transmission blocking malaria vaccine are focused on the production of TBV in plant-based expression system with a good safety profile, which are capable of inducing a strong immune response to reduce the malaria transmission717374. Completed clinical trials with Pfs25 formulations have been found immunogenic but shown some safety outcome issues like local and systemic adverse events8182.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, many efforts for the development of transmission blocking malaria vaccine are focused on the production of TBV in plant-based expression system with a good safety profile, which are capable of inducing a strong immune response to reduce the malaria transmission717374. Completed clinical trials with Pfs25 formulations have been found immunogenic but shown some safety outcome issues like local and systemic adverse events8182.…”
Section: Discussionmentioning
confidence: 99%
“…The plant-based expression system provides all the advantages of a eukaryotic expression system with high purity and stability. Various TBV candidates have been successfully produced in plant system707172 with high recovery and desired immunogenicity (Table IV). Algae are also a promising system for the production of TBV that are orally delivered to avoid expensive purification and injectible delivery737475.…”
Section: Production Of Tbvs In Plant Based Systemmentioning
confidence: 99%
“…Sig, significant. observed with another plant-based method with hydroponic Nicotiana (14,39). Microalgae and single-celled waterborne plants grow much more rapidly than more complex plants and can be cultured under cyclic GMP (cGMP) conditions at low cost (50).…”
Section: Figmentioning
confidence: 99%
“…The many different systems, i.e., E. coli (10), tobacco (38,39), Saccharomyces cerevisiae (11,37,40,41), Pichia pastoris (12,42), DNA vaccines (43,44), wheat germ (15), insect cells via baculovirus (13,16), protein-peptide conjugates (45), Pseudomonas aeruginosa ExoProtein A (rEPA) (46), cholera toxin adjuvant (12), and virally vectored vaccines (47,48), by which recombinant Pfs25 has been produced have uniformly found that recombinant Pfs25 administered in animal models in the absence of adjuvant is poorly immunogenic, with relatively low IgG titers. The importance of a safe and effective adjuvant for Pfs25-regardless of the heterologous expression system-was highlighted in a phase I clinical trial in which Montanide IS151 combined with Pichia-produced Pfs25 was associated with leukemoid reactions and erythema nodosum in humans (21).…”
Section: Figmentioning
confidence: 99%
“…More recently some of these limitations may have been successfully addressed. Potent transmission blocking activity was obtained in pre-clinical immunization studies using purified codon-harmonized Pfs25 expressed in E. coli [54], with Pfs25 produced in chloroplasts of algae [55] Pfs25-IMX313 nanoparticles in Pichia pastoris [56] or with Pfs25 fused to a modified lichenase (LicKM) carrier in Nicotiana benthamiana plants [57]. Another promising approach for enhancing Pfs25 immunogenicity is conjugation to carrier proteins with known high immunogenicity e.g.…”
Section: Pfs25mentioning
confidence: 99%